2021
DOI: 10.3390/jcm10173976
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Eating Disorder Examination Questionnaire in Danish Eating Disorder Patients and Athletes

Abstract: The Eating Disorder Examination Questionnaire (EDE-Q) is a gold standard questionnaire to identify eating disorder symptoms but has not yet been validated in Danish. The scale consists of four theoretical constructs of disordered eating: Restraint eating, Eating concerns, Shape concerns and Weight concerns. However, the four-factor structure has been difficult to replicate across cultures. This study aimed to examine the factor structure and psychometric properties of the EDE-Q in Danish. The study consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…A global EDE-Q score ≥ 2.5 was used to classify athletes with disordered eating behavior (Rø et al, 2015 ; Kuikman et al, 2021 ). The EDE-Q has been validated in an athletic population with Cronbach's Alpha coefficients ranging from 0.81 to 0.91 in the subscales (Lichtenstein et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…A global EDE-Q score ≥ 2.5 was used to classify athletes with disordered eating behavior (Rø et al, 2015 ; Kuikman et al, 2021 ). The EDE-Q has been validated in an athletic population with Cronbach's Alpha coefficients ranging from 0.81 to 0.91 in the subscales (Lichtenstein et al, 2021a ).…”
Section: Methodsmentioning
confidence: 99%
“…This is lower than what is typically seen in clinical samples (e.g. global scores of 3.92–3.98; Jennings & Phillips, 2017 ; Lichtenstein et al., 2021 ) but higher than what is typically observed in non‐clinical, community athlete samples (e.g. global scores of 0.89–2.50; Gorrell et al., 2021 ; Lichtenstein et al., 2021 ).…”
Section: Discussionmentioning
confidence: 65%
“…global scores of 3.92–3.98; Jennings & Phillips, 2017 ; Lichtenstein et al., 2021 ) but higher than what is typically observed in non‐clinical, community athlete samples (e.g. global scores of 0.89–2.50; Gorrell et al., 2021 ; Lichtenstein et al., 2021 ). This confirms that participants in our study reported experiencing mild eating disorder symptoms.…”
Section: Discussionmentioning
confidence: 92%
“…Binge-Eating Disorder Questionnaire ( BED-Q ) ( Jensen et al, 2020 ; Lichtenstein et al, 2021 ) is a 9-item questionnaire. Items 1–7 make up the sum score (0–35).…”
Section: Methodsmentioning
confidence: 99%